Offenbarung des Johannes und Archäologie - Hasitschka, Martin (Protokolle zur Bibel, 2005)
The letters to the seven churches in the book of Revelation indicate that the Christians in Western Asia Minor at the end of the first century were confronted in different ways both with the cultural and religious pluralism of the pagan environment and with Diaspora-Judaism. Ephesus, Pergamon and Sardes are taken as examples to show how archaeological research helps to illustrate the different religious cults and especially the emperor worship by which the Christians were challenged.